2021
DOI: 10.3389/fgene.2021.796211
|View full text |Cite
|
Sign up to set email alerts
|

A Chromosome-Level Genome Assembly of Mozambique Tilapia (Oreochromis mossambicus) Reveals the Structure of Sex Determining Regions

Abstract: The Mozambique tilapia (Oreochromis mossambicus) is a fascinating taxon for evolutionary and ecological research. It is an important food fish and one of the most widely distributed tilapias. Because males grow faster than females, genetically male tilapia are preferred in aquaculture. However, studies of sex determination and sex control in O. mossambicus have been hindered by the limited characterization of the genome. To address this gap, we assembled a high-quality genome of O. mossambicus, using a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…In 2015, the genomes of Nile tilapia and O. mossambicus were resequenced 83 . The draft genome of O. mossambicus was published by Tao et al, 84 but the genome has not yet been well annotated. The draft genome assembly of O. mossambicus is approximately 1 Gb with a N50 (genome 50% present in fragments of this length) of 11.4 Mb (megabase).…”
Section: Status Of Breeding Salinity‐tolerant Tilapiamentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, the genomes of Nile tilapia and O. mossambicus were resequenced 83 . The draft genome of O. mossambicus was published by Tao et al, 84 but the genome has not yet been well annotated. The draft genome assembly of O. mossambicus is approximately 1 Gb with a N50 (genome 50% present in fragments of this length) of 11.4 Mb (megabase).…”
Section: Status Of Breeding Salinity‐tolerant Tilapiamentioning
confidence: 99%
“…In 2015, the genomes of Nile tilapia and O. mossambicus were resequenced. 83 The draft genome of O. mossambicus was published by Tao et al, 84 35 A total of 23,117 protein-encoding genes was predicted. The study found that predicted antimicrobial peptides were highly similar among Nile and blue tilapias.…”
Section: Genomic Tools and Resources Available For Salinity-tolerant ...mentioning
confidence: 99%
See 1 more Smart Citation